APLIKASI EDIBLE COATING LIDAH BUAYA (Aloe vera L.) DENGAN PENAMBAHAN KARAGENAN TERHADAP KUALITAS BUAH JAMBU BIJI (Psidium guajava L.) - TOHA ABDUL KOHAR; YUSMARINI YUSMARINI; DEWI FORTUNA AYU (Jurnal Sagu, 2018)
Edible coating application serves to replace a layer of natural waxes lost due to post harvest handling. Thisstudy aims to determine the effect of concentration of carrageenan in edible coating solution of aloe vera on thequality of guava fruit during storage. This study used a completely randomized design, which consists of fivetreatments and three replications. The treatments were K0 (without addition of carrageenan), K1 (addition ofcarrageenan 0.1%), K2 (addition of carrageenan 0.2%), K3 (addition of carrageenan 0.3%), and K4 (addition ofcarrageenan 0.4%). Data were analyzed using analysis of variance followed by Duncan’s New Multiple RangeTest at 5% level. The results showed that the addition of various concentrations of carrageenan in aloe veraedible coating applied to guava fruit significantly affected the weight loss, hardness, total dissolved solids,vitamin C, and skin colour of guava fruit, but did not significantly affect the colour of flesh and flavour of guavafruit in hedonic assessment. The best treatment for maintaining the quality of guava fruit during storage was thetreatment K4 with the addition 0.4% carrageenan. The treatment K4 had weight loss 7.30%, hardness 6.11 kg/f,total soluble solids 3.39obrix, and vitamin C 173.70 mg/100 g. Hedonic sensory assessment of the skin colour ofguava fruit had value 2.19 (like), colour of guava fruit flesh had value 2.01 (like), and flavour of guava fruit hadvalue 2.10 (like).